If $a,b,c$ are nonnegative real numbers such that $a+b+c=3,$ then

$$(a^2+bc^4)(b^2+ca^4)(c^2+ab^4) \leq 64$$

My try: I found the equality holds only if $(a,b,c)=(2,0,1)$ or all of its permutations.

But I can't prove this inequality it. I would appreciate very much a proof.

This problem comes from:http://www.artofproblemsolving.com/Forum/viewtopic.php?f=52&t=562119

  • 2
    $\begingroup$ Do you mean "I found that equality holds only if $(a,b,c)$ is $(2,0,1)$, $(1,2,0)$, or $(0,1,2)$"?. $\endgroup$ Nov 13 '13 at 11:05
  • $\begingroup$ If you can prove one of them is zero, then you can just study $f(2+x,0,1-x)$ and see that its maximum is $64$. $\endgroup$ Nov 13 '13 at 12:20
  • $\begingroup$ You can edit your question so that it says what you mean. $\endgroup$ Nov 13 '13 at 12:26
  • $\begingroup$ @math110: I've taken the liberty of editing it for you. Where did you get this question from, if you don't mind me asking. $\endgroup$
    – Nick
    Nov 13 '13 at 13:05

enter image description here   →  enter image description here   →   enter image description here

The three dimensional problem can be simplified to a two dimensional problem by introducing (again and again) suitable triangle coordinates: $$ \left[ \begin{array}{c} a \\ b \\ c \end{array} \right] = \left[ \begin{array}{c} 3 \\ 0 \\ 0 \end{array} \right] + \left[ \begin{array}{c} -3 \\ 3 \\ 0 \end{array} \right] x + \left[ \begin{array}{c} -3 \\ 0 \\ 3 \end{array} \right] y $$ Then the equation $(a^2+bc^4)(b^2+ca^4)(c^2+ab^4) \leq 64$ does not so much "simplify", but anyway becomes an equation in two variables (2-D). And the equation $\;a + b + c = 3\;$ corresponds with a normed 2-D triangle, with vertices $(0,0),(1,0),(0,1)$ . The insides of both can easily be visualized, as has been done in the above picture in the middle:
$\color{red}{red}$ for $\;a + b + c = 3\;$ and $\color{green}{green}$ for $\;(a^2+bc^4)(b^2+ca^4)(c^2+ab^4) \leq 64\;$ .
The transformed inequality is: $$\left[ 3^2\left( 1-x-y \right)^{2} + 3^5\,x{y}^{4} \right] \left[ 3^2\,{x}^{2} + 3^5\,y \left( 1-x-y \right)^{4} \right] \left[ 3^2\,{y}^{2} + 3^5\, \left( 1-x-y \right){x}^{4} \right] \le 64 $$

It is seen in the same picture that the edge $\;y=1-x\;$ of the triangle maybe is tangent to the curve $(a^2+bc^4)(b^2+ca^4)(c^2+ab^4) = 64$ . Indeed, if we substitute $y=1-x$ into (the transformation of) that equation and simplify, then we get: $$ 3^9\, x^3 (1-x)^6 - 64 = 0 $$ The same sort of equation is found with the substitutions $\,x=0\,$ or $\,y=0\,$, for the other two edges. And, as has been found by others, there is only one solution of that equation, within the specified range, namely $x=1/3$, corresponding with $y=2/3$ and hence $(a,b,c) = (0,1,2)$ . And of course any cyclic permutation of this, due to symmetry. The rest of the (red) triangle $\;a + b + c = 3\;$ is well within the (green) area of $\;(a^2+bc^4)(b^2+ca^4)(c^2+ab^4) \leq 64$ . Which can be shown by plotting the triangle first: then it becomes absorbed by the green area (see picture on the right).

Analytically, the proof is completed by considering the function $\;f(x) = 3^9\, x^3 (1-x)^6$ .
Its extreme values are found for $\;f'(x) = x^2(1-x)^5(3-9x)=0$ , giving $\;x = \{0,1,1/3\}$ , with the maximum $\;f(1/3)=64$ .

The picture on the right shows the the inequality as observed in the plane $\;a + b + c = 3\;$ of the triangle in 3-D (picture on the left). Mind the symmetries.

  • $\begingroup$ Can you use other colors? Since many people have protanopia or protanomaly (like me). $\endgroup$
    – ziyuang
    Jan 8 '14 at 11:24
  • 1
    $\begingroup$ Next time, I promise. Any suggestion? I've used red and green now. $\endgroup$ Jan 8 '14 at 14:45
  • $\begingroup$ Maybe different patterns of lines, if that's convenient for you. $\endgroup$
    – ziyuang
    Jan 8 '14 at 23:05

Without loss of generality, assume $a$ is smallest of $a, b, c$. Also, let $$f(a,b,c)=(a^2+bc^4)(b^2+ca^4)(c^2+ab^4)$$and firstly, if $a\le c\le b$, then$$f(a,b,c)-f(a,c,b)=(b^3-a^3) (c^3 - a^3) (b ^3- c^3) (a b c - 1)<0$$therefore we can assume $a\le b\le c$. Now, we will prove $$f(0,b,a+c)\ge f(a,b,c)$$which is, after full expansion,$$a (-a^6 b^4 c + a^5 b^3 - a^5 c^3 - a^4 b^5 c^5 - a^3 b c^7 - a^2 b^6 + 20 a^2 b^3 c^3 \\+ 15 a b^3 c^4 - a b^2 c^2 - b^7 c^4 + 6 b^3 c^5)+ 6 a^5 b^3 c + 15 a^4 b^3 c^2\ge0$$ and it is obvious that $-a^6 b^4 c + a^5 b^3\ge0$, $- a^5 c^3 - a^4 b^5 c^5 - a^2 b^6 + 20 a^2 b^3 c^3\ge0$ and $6 a^5 b^3 c + 15 a^4 b^3 c^2\ge0$. Therefore it is enough to show$$b c^2 (-a^3 c^5 + 15 a b^2 c^2 - a b - b^6 c^2 + 6 b^2 c^3)\ge0$$and from $-a^3c^5\ge-ab^2c^5$, $-ab\ge-abc^3\ge-b^2c^3$ and $-b^6c^2>-4b^3c^2\ge-4b^2c^3$, it is left to show$$b^2c^2(-a c^3 + 15 a + c)\ge0$$and we can divide it with three cases.

Case 1) $c^3\le15$: $-a c^3 + 15 a + c>a(15-c^3)\ge0$.

Case 2) $15^{1/3}< c\le2.6$: Firstly, $c>2.4$. The equation is decreasing with respect to $a$, therefore we need to show only for maximal value of $a$. If $a>0.3$, then $a+b+c\ge2a+c>0.6+2.4=3$, so maximal value is $0.3$. Also, $c^3\le2.6^3<20$. Therefore, $$-a c^3 + 15 a + c\ge0.3(15-c^3)+c\ge-1.5+2>0$$

Case 3) $2.6<c\le3$: Similarly, it is enough to show for maximal value of $a$ which is $0.2$. Therefore, $$-a c^3 + 15 a + c\ge0.2(15-27)+2.6>0$$

Therefore, we can assume that $0=a\le b\le c$. Now $f(a,b,c)=b^3c^6\le2^6\left(\frac{3\times b+6\times0.5c}{9}\right)^9=64$ and it is proved.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.